(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
The Hunger Games series was banned to begin with before even it became a cult classic because of its anti-family concerns, the rebellion and the attitude of challenging the governmental authority. The system of futuristic governance is a warning to the readers, especially the teens of tomorrow as to how their lives would be in future if they continue to remain complacent about the ways of the authorities who rule them over. There is crime, retribution and rebellion each of which has its causes, consequences and repercussions. The paper aims to look at the struggle for food which Katniss and Dale confront to take care of their families written in the language of the future. The words which the author has coined for the future and the shades of meaning that they give are also highlighted.